1994
DOI: 10.1148/radiology.191.3.8184046
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of pleural effusions: sonography versus radiography.

Abstract: In quantification of pleural effusions, the sonographic measurement method presented is preferable to radiographic measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
187
2
16

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(207 citation statements)
references
References 0 publications
2
187
2
16
Order By: Relevance
“…Scans of the basal pleurae and the diaphragm should be obtained with the patient seated and then (when possible) in the supine position. In rare cases, the patient may be asked to stand during the examination (e.g., when the costophrenic recess is being explored for a possible effusion) [6,7]. Various scanning planes can be used: intercostal, longitudinal, transversal, and paravertebral scans can be used to explore the posterior chest wall, whereas the anterior wall is usually investigated with intercostal, longitudinal, supra-and parasternal, sub-xiphoid, and supraclavicular scans.…”
Section: Techniquementioning
confidence: 99%
“…Scans of the basal pleurae and the diaphragm should be obtained with the patient seated and then (when possible) in the supine position. In rare cases, the patient may be asked to stand during the examination (e.g., when the costophrenic recess is being explored for a possible effusion) [6,7]. Various scanning planes can be used: intercostal, longitudinal, transversal, and paravertebral scans can be used to explore the posterior chest wall, whereas the anterior wall is usually investigated with intercostal, longitudinal, supra-and parasternal, sub-xiphoid, and supraclavicular scans.…”
Section: Techniquementioning
confidence: 99%
“…In recent years, studies have shown that sonography achieves better results than radiography in measuring the effusion volume. [8][9][10][11] However, the confidence intervals for such measurements remain wide. For this reason, and because of the heterogeneity of the methods proposed in different studies, large-scale use of sonography has been impeded.…”
Section: Introductionmentioning
confidence: 99%
“…Since previous studies have established a method of correlating measurements between LDR and ultrasound [12], and between LDR and LER [8], it should be possible to define a correlation between measurements with LDR and CCT. This measurement can be used to define the need for thoracentesis once a PPE is documented by CCT.…”
mentioning
confidence: 99%